2020
DOI: 10.25081/jebt.2020.v12.6434
|View full text |Cite
|
Sign up to set email alerts
|

Control of filariasis vector using Ovillanta in Gwale local Government area of Kano State, Nigeria

Abstract: The study was aimed at finding the effectiveness of a physical method of controlling filariasis vector larvae. Four ovillanta traps were placed in four different sites (north, south, west and east) of Gwale Local Government area of Kano state. The eggs and immature stage(larvae) of the filariasis vector were collected and destroyed. A total of 134667 larvae were collected altogether. 25% from site A, 23% from site B, 28% from site C and 24% from site D.The finding of the study shows that ovillanta trap is an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…A random sampling technique was used to select three agricultural farmland from which soil samples were col lected in Kura Local Government Area of Kano, North western Nigeria, located at 11°46´N, 8°49´E and 12°01´N, 8°29´E (Umar et al 2020). Soil samples were collected at the depth of 5-10 cm below the topsoil using a ster ile scoop after removal of the top layer of the soil up to 1-5 cm.…”
Section: Sample Collectionmentioning
confidence: 99%
“…A random sampling technique was used to select three agricultural farmland from which soil samples were col lected in Kura Local Government Area of Kano, North western Nigeria, located at 11°46´N, 8°49´E and 12°01´N, 8°29´E (Umar et al 2020). Soil samples were collected at the depth of 5-10 cm below the topsoil using a ster ile scoop after removal of the top layer of the soil up to 1-5 cm.…”
Section: Sample Collectionmentioning
confidence: 99%
“…The Ovillanta is a simple trap for mosquito oviposition consisting of portions of vehicle tires with water in them. Manual removal and destruction of larvae from the traps was shown to be effective in preliminary trials, but population effects have yet to be shown (Ulibarri et al 2016, Umar et al 2020. Behavioral manipulation is achieved through the use of pheromones associated with those behaviors, this includes aggregation, disaggregation and mate seeking.…”
Section: Disease Vector Control Practicesmentioning
confidence: 99%